The Effect of Fundamental Variables and Sales Growth on Stock Prices in Wholesale Sub- Sector Companies - Agustinus Zai; Melly Darniati Laia; Tri Muthia Ashri; Sastira Sugania; Thomas Firdaus Hutahaean (Journal of Research in Business, Economics, and Education, 2021)
This study aims to explain the effect of Fundamental variables represented by Return on Assets (X1), Current Ratio (X3) Debt to Equity Ratio (X4) and Sales Growth on Stock Prices. with purposive sampling technique. This study uses secondary data with classical assumption test and multiple regression analysis. The results showed that simultaneously the fundamental variables represented by Return on Assets (X1), Current Ratio (X2), Debt to Equity ratio (X3) and Sales Growth (X4) had a significant and significant effect on stock prices. Partially, the mental fund variable represented by Return on Assets has a significant and significant effect on stock prices. While the mental fund variables represented by the Current Ratio, Debt to Equity Ratio and Sales Growth partially have no effect and are not significant to stock prices. The Coefficient of Determination (R2) value of Adjusted R Square is 0.403 (40.3%). So the influence of the fundamental variables represented by Return On Assets (X1), Current Ratio (X2), Debt to Equity ratio (X3) and Sales Growth (X4) on stock prices is 40.3%. The remaining 59.7 percent is influenced by other variables not examined in this study.